Assessing Impact of Household Intervention on Indoor Air Quality and Health of Children with Asthma in the US-Mexico Border: A Pilot Study. (3rd August 2020) - Moreno-Rangel, Alejandro; Baek, Juha; Roh, Taehyun; Xu, Xiaohui; Carrillo, Genny
Abstract : Few studies have investigated household interventions to enhance indoor air quality (IAQ) and health outcomes in relatively low-income communities. This study aims to examine the impact of the combined intervention with asthma education and air purifier on IAQ and health outcomes in the US-Mexico border area. An intervention study conducted in McAllen, Texas, between June and November 2019 included 16 households having children with asthma. The particulate matter (PM2.5 ) levels were monitored in the bedroom, kitchen, and living room to measure the IAQ for 7 days before and after the intervention, respectively. Multiple surveys were applied to evaluate changes in children's health outcomes. The mean PM2.5 levels in each place were significantly improved. Overall, they significantly decreased by 1.91  μ g/m 3 on average (p < 0.05 ). All surveys showed better health outcomes; particularly, quality of life for children was significantly improved (p < 0.05 ). This pilot study suggests that the combined household intervention might improve IAQ in households and health outcomes for children with asthma and reduce health disparities in low-income communities. Future large-scale studies are needed to verify the effectiveness of this household intervention to improve IAQ and asthma management.